Basal cell carcinoma – diagnosis - Mackiewicz-Wysocka, Małgorzata; Bowszyc-Dmochowska, Monika; Strzelecka-Węklar, Daria; Dańczak-Pazdrowska, Aleksandra; Adamski, Zygmunt (Contemporary Oncology/Współczesna Onkologia, 2013)
Basal cell carcinoma is the most common skin cancer in the Caucasian population. The cancer arises in sun exposed areas of the skin. The incidence of morbidity is high and it is still growing. The metastatic rate is low, but the enlarging tumor may cause severe tissue disfigurement and a poor cosmetic outcome. The diagnosis is usually clinical but there are many subtypes of this carcinoma and correct diagnosis is the clue to appropriate treatment of the lesion. The main problem in basal cell carcinoma management is the high recurrence rate.